Simulator for Teaching Computed Tomography Principle - Voda, Petr; Kordek, David; Jezbera, Daniel; Masopust, Pavel; Bezrouk, Ales (Jurnal Pendidikan Fisika Indonesia, 2024)
Computed tomography (CT) is one of the most important imaging methods in clinical medical practice. Students of medicine have an opportunity to learn about its principles during the classes of the medical biophysics. For a high-quality understanding of the function of CT and to increase the curriculum attractiveness, it is advisable to include such clinical equipment or its simulator in the practical lessons. However, regarding operational safety and related maintenance, CT devices are very expensive and demanding. Therefore, the aim of this work was to create a cheap, operationally easy, and safe CT simulator. The device simulates the principle of CT by transmitting visible light through cubes with a built-in filter of defined attenuation simulating various human tissues. During hands-on training, students first measure radiation intensities without a sample (I0) and with single cubes (Ii). In the second task, students measure a matrix consisting of four different cubes, irradiating the matrix from different directions and simulating the CT principle. Based on the measurements, the students calculate the linear attenuation of each cube and the corresponding CT numbers and compare the results. The simulator's control is intuitive, provided measurement results are consistent and automatically fed into an interactive report that compares the measured data with the students' calculations, verifies the results, and finally stores them in the database. The main benefit of the study is to bring cheap and effective tools for the demonstration of the CT principle, which can operate each student during the practical lessons, followed by supporting teaching materials.